Strength Analysis of Basalt Epoxy Composite Laminates with Multiple Open Holes - Supparmaniam, Veenoshini (2018)
Basalt is a naturally occurring material that is abundant beneath the Earth’s crust and can be used as reinforcing material of a composite laminate. In this project, epoxy is used as the matrix and basalt fibers are used as the reinforcing fibers. These basalt composites are majorly used as the skin of aircrafts. However, the arrangement of the holes drilled onto these composites to fasten it to the frame is to be determined. Thus, the strength of basalt fiber composites are investigated numerically and experimentally when multiple holes of different orientations are present. Numerical analysis is done on the samples containing multiple open holes with different distances using ANSYS 19.0. Then, the simulation is verified experimentally by tensile test. The samples for the tests are fabricated locally in the laboratory of Universiti Teknologi PETRONAS by hand lay-up method and then is sheared into samples according to the testing standards and are tested. The standards used for the tests are ASTM D5766 for tensile test and ASTM D6641 for compressive test. The results show that the ratio of von Mises stress simulated for tensile test in sample A is 1.5 which is the lowest among all other samples. Among samples B, C, D and E, sample E has the highest ratio of von Mises stress to applied stress of 1.8. For the simulation of compressive test, the sample with the single open-hole had the lowest ratio of von Mises stress to applied stress of 2.4. Among the samples with three open-holes, sample E had the lowest ratio of 2.6. The experimental results show sample A had the highest tensile strength of 296 MPa. Among the samples with three open-holes, sample E had the highest tensile strength of 293 MPa. To validate the results of the simulation with the experimental results, modulus of elasticity of the samples are calculated. The modulus of elasticity of the simulation showed a similar pattern to the experimental data where sample A had the highest modulus of elasticity. Among samples B, C, D and E, sample E had the highest modulus of elasticity. In short, the strength of basalt epoxy composite laminates degrades more with the addition of more open-holes on the sample. However, the degradation of the strength can be reduced by increasing the distance between the open-holes.